A low ankle-brachial index is associated with cognitive impairment: The APAC study. (December 2016) - Wang, Anxin; Jiang, Ruixuan; Su, Zhaoping; Jia, Jiaokun; Zhang, Ning; Wu, Jianwei; Chen, Shengyun; Zhao, Xingquan
Abstract: Background and aims: Given the recognized links between atherosclerosis and cognitive impairment, the aim of this study was to examine the association between the ankle-brachial index (ABI) and cognitive impairment in a cross-sectional setting of a Chinese population. Methods: Participants (n = 3, 048, aged ≥40 years, 1727 men and 1321 women) were recruited from the ongoing community-based Asymptomatic Polyvascular Abnormalities Community Study. ABI was measured and a low ABI was defined as <0.9. Cognition status was evaluated via the Mini-Mental Status Exam. Multivariate logistic regression models and linear regression models were used to assess the association between ABI and cognitive impairment. Results: A low ABI was associated with cognitive impairment (odds ratio, OR = 1.983; 95% confidence interval, CI: 1.150–3.419), independent of the potential confounders. In addition, a decreasing ABI (per standard deviation) was significantly associated with cognitive impairment in fully adjusted models (OR = 1.156; CI: 1.013–1.319) and with a significant trend of decreasing MMSE scores (β = 0.703, 95% CI 0.189–1.218, p  = 0.0074). Furthermore, the odds of a low ABI associated with cognitive impairment in participants without hypertension and participants with diabetes were 4.924 (CI: 1.860–13.035) and 6.393 (CI: 2.431–16.810), respectively. Conclusions: A low ABI is associated with cognitive impairment, especially in non-hypertensive and diabetic patients. Graphical abstract: Highlights: A low ABI is associated with cognitive impairment, independent of age, gender, education level and common vascular risk factors. This association is pronounced in the non-hypertensive population and in the diabetic population. Highlighting the interest of using ABI to assist identifying individuals at higher risk of cognitive disorders, further research in this topic is needed.